Cultural Identity Construction and Intercultural Communication in a Digital Era - Liu, Yijun (Auckland University of Technology, 2024)
Fandom subtitling, or ‘fansubbing’, is a form of online subtitling activity “by fans for fans”. Emerging in participatory culture, numerous Chinese fans of American movies or television programmes voluntarily subtitle and distribute media content online for their peers worldwide. In 2006, various fansubbing groups (fansubs) were formed, and members began to subtitle American television programmes and other foreign media content for Chinese audiences online. As an interdisciplinary phenomenon of fandom culture and intercultural communication, fansubbing has become a topic of interest for researchers. However, fan subtitlers have rarely been researched for several reasons, such as their subcultural nature, anonymity, legality, and ethical concerns. This thesis critically examines the multiple identities formed by four Chinese fansubs, understood as representing an online community of practice, and explores fan subtitlers’ perceptions of their roles. The research analyses fansubs’ media texts and how Chinese fan subtitlers’ reflective thinking is played out in their identity construction, focusing on the tensions and contradictions arising from the perspectives and actions of multiple agencies, including industries, governments and fansubs. In data collection, this research applies a netnographic approach, questionnaires, and interviews to investigate six identities exhibited by fansub members: collective, prosumer, resistant, pirates, narcissist, and cultural transmitter. The findings show that fan subtitlers’ identity traits are displayed in groups through various mechanisms, regulations, development, and text manipulation. Chinese online fansubbing groups play their roles tactfully, and their members cautiously manage their identities online. The research extends the understanding of online fandom culture and the fan subtitlers’ hybrid identities. It provides significant insights into online fan audiences and could be a useful reference for scholars interested in exploring fandom within an interdisciplinary framework. It should be noted that studying the identity construction and characteristics of fansub groups provides a new perspective on fandom communities as representing both new audiences and mass media online culture against the background of today’s media environment.